New venture creation – the influence of entrepreneurship education on students’ behavior (a literature – review based study) - Kazmi, Syed Zaheer Abbas; Nábrádi, András (Applied Studies in Agribusiness and Commerce, 2017)
Entrepreneurship brings economic growth and development through the process of venture creation. These new business enterprises have a very important and positive impact on employment generation, poverty alleviation, and socio-economic development. Entrepreneurship education influences the attitude and behavior of students to form intentions of self-employability. We have analyzed the literature to clearly understand the relationship between entrepreneurship education and intentionality and the underlying mechanisms through which entrepreneurship education impacts intentions to start new ventures. By utilizing the Theory of Planned Behavior (TPB) and Social Cognitive Theory (SCT), we propose that entrepreneurship education increases students’ perceived entrepreneurial self-efficacy and perceived desirability for starting new ventures. Entrepreneurial self-efficacy and desirability in turn impact and increase students’ entrepreneurial intentions for creating new ventures. Entrepreneurship Education Programs (EEPs) focusing “Education for entrepreneurship” have more influence on intentionality through self-efficacy and desirability. Comparatively, EEPs concentrating on “Education about entrepreneurship” will have less impacts on the intentionality. The study has important theoretical and practical implications for researchers, academicians, policy makers and potential entrepreneurs – the students. JEL. Code: A2, L6